Research on Energy Flow Testing and Optimization of Pure Electric Vehicles - Wei, Songmao; Wang, Yuan; Zhao, Yuntong (Scientific Journal of Technology, 2026)
In recent years, new energy vehicles have achieved leapfrog development, yet energy consumption performance remains a critical bottleneck affecting user experience. The energy consumption issue in electric vehicles is essentially a concentrated reflection of the efficiency of energy conversion, storage, and utilization under complex working conditions and system interactions. For example, the remaining driving range is typically estimated dynamically based on instantaneous energy consumption. Factors such as rapid acceleration, air conditioning use, and low-temperature environments can easily cause a sharp drop in the displayed range, leading to range anxiety among users. Additionally, comfort features such as large screens, premium audio systems, ambient lighting, and seat heating/ventilation continuously consume electrical energy. Against this backdrop, energy flow testing has become an important method for unveiling the "black box" of energy transfer and breaking down macroscopic range anxiety into specific optimizable components. By testing and analyzing the energy flow within the vehicle, high-loss nodes can be accurately identified, thereby providing a clear basis for system-level energy efficiency optimization. This paper takes a pure electric heavy-duty truck as the research subject, conducts real-vehicle energy flow testing and in-depth analysis, with the aim of providing insights for optimizing the vehicle’s energy management strategy.